2013
DOI: 10.1186/1476-4598-12-168
|View full text |Cite
|
Sign up to set email alerts
|

Podoplanin expression in cancer-associated fibroblasts enhances tumor progression of invasive ductal carcinoma of the pancreas

Abstract: BackgroundInteractions between cancer cells and surrounding cancer-associated fibroblasts (CAFs) play an important role in cancer progression. Invasive ductal carcinoma (IDC) of the pancreas is characterized by abundant fibrous connective tissue called desmoplasia. Podoplanin (PDPN) is a lymphatic vessel marker (D2-40), and expression of PDPN by stromal CAFs has been reported to be a prognostic indicator in various types of cancer.MethodsExpression of PDPN in pancreatic IDCs was assessed by immunohistochemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
90
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 131 publications
(104 citation statements)
references
References 47 publications
3
90
1
2
Order By: Relevance
“…They have illustrated that cancer cells invade by following the CAFs into the matrix. However, these studies have assayed CAFs as a uniform population, while a diversity of phenotypes and functions in CAFs have been reported in other studies . In this study, we demonstrated that CAFs expressing PDPN invaded a collagen matrix to a greater extent and enhance the local invasion of cancer cells.…”
Section: Discussionmentioning
confidence: 52%
“…They have illustrated that cancer cells invade by following the CAFs into the matrix. However, these studies have assayed CAFs as a uniform population, while a diversity of phenotypes and functions in CAFs have been reported in other studies . In this study, we demonstrated that CAFs expressing PDPN invaded a collagen matrix to a greater extent and enhance the local invasion of cancer cells.…”
Section: Discussionmentioning
confidence: 52%
“…Immunohistochemical staining was performed as described previously . Briefly, FFPE tissue samples were sliced and deparaffinized with xylene and ethanol.…”
Section: Methodsmentioning
confidence: 99%
“…Podoplanin, which binds to the platelet aggregation‐stimulating domain of PDPN–C‐type lectin‐like receptor 2 in platelets, induces platelet aggregation, resulting in cancer metastasis . Furthermore, high expression of podoplanin in cancer‐associated fibroblasts is associated with severe malignancy and poor prognosis in cancer patients . Therefore, it is expected that podoplanin will become a target for cancer diagnosis and therapies.…”
mentioning
confidence: 99%
“…(4,10) Furthermore, high expression of podoplanin in cancer-associated fibroblasts is associated with severe malignancy and poor prognosis in cancer patients. (11)(12)(13)(14) Therefore, it is expected that podoplanin will become a target for cancer diagnosis and therapies.Malignant pleural mesothelioma, which is mainly caused by exposure to asbestos, develops in the pleural cavity with a high likelihood of malignancy. (15) It is expected that the number of MPM patients will increase from 2030 to 2040 in Asia, and from 2010 to 2020 in Europe.…”
mentioning
confidence: 99%
See 1 more Smart Citation